2014
DOI: 10.1016/j.ijmyco.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three immunological tests for the diagnosis of pulmonary tuberculosis in a rural endemic area of Bangladesh

Abstract: Considering the resource-constraints of rural and remote areas, the Mantoux test could be an alternative tool for the diagnosis of active PTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this study, admitted patients were tested with Mantoux test and 95% had MT positive (Figure-I) and found highly sensitive though it has false positive and false negative with some issues and cannot confirm diagnosis, it helped making initial screening and a route to diagnosis. In Islam MT Mantoux test was found more sensitive tool and 96% was found positive for TB 21 . In another study by Singh S, it was found similar result of MT and was 94.3% positive for TB and was highly sensitive 22 .…”
Section: Discussionmentioning
confidence: 89%
“…In this study, admitted patients were tested with Mantoux test and 95% had MT positive (Figure-I) and found highly sensitive though it has false positive and false negative with some issues and cannot confirm diagnosis, it helped making initial screening and a route to diagnosis. In Islam MT Mantoux test was found more sensitive tool and 96% was found positive for TB 21 . In another study by Singh S, it was found similar result of MT and was 94.3% positive for TB and was highly sensitive 22 .…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, a test able to diagnose LTBI or incipient active TB (iATB) would greatly improve early diagnosis, assist with patient management programs, reduce disease dissemination and the current socioeconomic disease burden (16)(17)(18). There is therefore clearly an urgent need for the development of rapid, inexpensive and accurate tests for diagnosis of TB particularly in the point of care (POC) and remote settings (19)(20)(21)(22)(23). A biomarker protein-based, non-sputum diagnostic test such as an LFD would fulfil these criteria.…”
Section: Introductionmentioning
confidence: 99%